Hysteresis observation of CoFe and CoFeB model disk using micromagnetic simulation. Issue 1 (February 2020) - Mustaghfiroh, Q; Djuhana, D; Kurniawan, C
Abstract: In this work, hysteresis loop of CoFe and CoFeB disk ferromagnets are observed by using micromagnetic simulation OOMMF based on LLG equation. The diameter varied from 50–500 nm with the thickness 5 nm and 10 nm. For simulation process, the damping factor of 0.05 and the cell size 2.5 × 2.5 × 2.5 nm 3 were fixed. We applied parallel and perpendicular external field to generate hysteresis loop of CoFe and CoFeB disk ferromagnets. Interestingly, we found two behaviours of coercivity, first less than diameter 100 nm and second, greater than 100 nm. For parallel-applied field of CoFe and CoFeB, the coercivity showed fluctuation around 20–160 mT. Greater than diameter 100 nm, the coercivity in a constant value around 40 mT for CoFe and around 20 mT for CoFeB. For perpendicular applied field of CoFe, we still observed the coercivity around 40 mT but greater than 100 nm, the coercivity dropped to zero. For CoFeB with perpendicular applied field, the coercivity decrease as the diameter increase until reach diameter 100 nm. Greater than the diameter 100 nm, the coercivity is constant at 20 mT. According to the results, we had observed the Perpendicular Magnetic Anisotropy (PMA) behaviour in both CoFe and CoFeB disk ferromagnets with certain value of the coercivity when the field applied in perpendicular direction.